Penggunaan Pupuk Organik Cair Kotoran Kambing untuk Meningkatkan Pertumbuhan Tanaman Jagung (Zea mays L.) - Rizka Rahmahwati; Hasrin (Universitas Muslim Buton, 2024)
Corn (Zea mays L.) is one of the important food crops in Indonesia and has a strategic role in the Indonesian national economy as the main food crop which not only provides food, but is also a source of animal feed and industrial raw materials. This research aims to determine the effect of applying liquid organic fertilizer from goat manure to increase the growth of corn plants (Zea mays L.). This study used a randomized block design consisting of four treatments and three replications, namely control treatment (J0), 50 mL/L (J1), 100 mL/L (J2) and 150 mL/L (J3). The research stages are preparation of materials, making liquid organic fertilizer from goat manure, planting corn, applying liquid organic fertilizer and maintenance. The results of research on plant height parameters showed that the highest plant height was in treatment J3 (150 mL/L) at 110.67 cm. The highest number of leaves was found in treatments J3 (150 mL/L) and J2 (100 mL/L), amounting to 10.00 and 10.67. The highest leaf area was in treatment J3 (150 mL/L) at 820.25 cm. Goat manure liquid fertilizer contains the nutrients N, P and K that plants need for plant height, number of leaves and leaf area. Key words: corn seeds, goat manure, fertilizer